Evaluation of metallophthalocyanine functionalized photocatalytic asymmetric polymer membranes for pollution control and antimicrobial activity - Mafukidze, Donovan Musizvinoda Chidyamurimi (Rhodes University, Faculty of Science, Department of Chemistry, 2021)
The conceptualisation of photosensitizing water treatment polymer membranes using phthalocyanine based photosensitizers is reported in this thesis. The key to successful preparation of stable photoactive polymer membranes was established as the covalent anchorage of the photosensitizer to a polymer, which was proven by singlet oxygen generation by the membranes without photosensitizer deterioration. Despite this limitation, the covalent linkage-incapable unsubstituted zinc (II) phthalocyanine (complex 2) was applied as a nanoconjugate of graphene quantum dots (2π(GQDs)). 2π(GQDs) was formed through π-π stacking, and was then covalently anchored, as a proof of concept. This concept was also applied to 2-(4-carboxyphenoxy) phthalocyaninato zinc (II) (complex 3) which is capable of covalent linkage but proved to deteriorate the efficiency of singlet oxygen formation with comparison to the covalent conjugates. Singlet oxygen generation by functionalized polymer membranes rendered them photocatalytic in the degradation of organic pollutants and microorganisms in water. Organic pollutant degradation capability was exemplified by 2π(GQDs) and a porphyrin-phthalocyanine heterodyad (complex 10) functionalized membranes (2π(GQDs)-memb and 10-memb respectively), where a MPc loading of approximately 0.139 μmol MPc/g of membrane was able to achieve a 4-chlorophenol degradation rate of 3.77 × 10−6 mol L−1 min−1 in a second order reaction with an initial 4-chlorophenol concentration of 3.24 × 10−4 mol L−1 for 2π(GQDs)-memb as an example. Antibacterial studies against S.aureus using a quaternized MPc and conjugates of silver triangular nanoprisms with zinc (II) and indium (III) MPcs showed note-worthy improvements in photodynamic antimicrobial chemotherapy (PACT) activity in comparison to the unquaternized MPc precursor, and the free zinc and indium MPcs respectively. Functionalization of polymer membranes with these higher activity photosensitizers translated to the formation of potentially superior biological fouling resistant membranes. The use of porphyrin-phthalocyanine polynuclei arrays (complex 10) in polymer membrane functionalization resulted in the use of a wider wavelength range (white light). The findings from this work as a whole, thus presents the potential applicability of phthalocyanine functionalized polymer membranes in water treatment technology.
Keywords: Photosensitizing compounds; Water -- Purification -- Photocatalysis; Phthalocyanines; Polymeric membranes; Porphyrins